Implementation of NAPTIP policy in Nigeria / Usman Mika’il Usman - Usman Mika’il , Usman (2020)
Human trafficking is a complex, clandestine and a global issue involving countries, as a source, transit or destination nations. Nigeria has been a severe source country. The exploitation of young females into sex trafficking in Nigeria is highly prevalent than other types of trafficking in the country. Fortunately, the government shows willingness and readiness to fight human trafficking. In this context, the passage of the first private bill saw the establishment of a National Agency for the Prohibition of Trafficking in Persons (NAPTIP) and other related matters in the year 2003. The NAPTIP Act is the primary policy document dealing with sex trafficking that shapes the implementation measures to protect, prevent, prosecute and assist trafficked victims. Accordingly, it is essential that this thesis tries to bridge the research gap by assessing human trafficking in light of the responses and impact to the stakeholders, especially government NAPTIP officers responsible for policy implementation of sex trafficking. This is a qualitative study that uses semi-structured interviews, observations, and document analysis of policy implementation in the aspect of sex trafficking in Nigeria. The study investigates the experiences of multiple actors. The informants are four female-trafficked victims, seventeen government NAPTIP officers, two academics and five non-governmental organisation representatives engaged in the human trafficking implementation of the policy. There are minimal empirical studies on human trafficking implementation of policy in Nigeria. Interestingly, concentrating on the NAPTIP officers as the primary implementers, this thesis contributes to and fills the gap to the improvement of policy implementation in light of the sex trafficking perspective. The feminist theory investigates the state of female exploitation, top-down and bottom-up theories examine the implementation process. These theories were distinguished as the basis for building up a conceptual framework to analyse and explain human trafficking: implementation of NAPTIP policy in Nigeria. The following five themes were apparent: socio-economic issues, socio-cultural issues, organisational issues, political issues, and policy issues. The investigation demonstrates the importance to address these variables that affect NAPTIP policy implementation. The research gives recommendations to the government of Nigeria to minimise the exploitative factors to female sex trafficking and improve the implementation process of human trafficking policy.